2014
DOI: 10.1113/jphysiol.2013.270108
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis decreases the sensitivity of pancreas‐projecting dorsal motor nucleus of the vagus neurones to group II metabotropic glutamate receptor agonists in rats

Abstract: Key pointsr Acute pancreatitis is one of the most severe disorders of the exocrine pancreas. r Pancreatic exocrine secretions (PES) are under regulatory control of dorsal motor nucleus of the vagus (DMV) neurones and their activity is regulated by inhibitory GABAergic and excitatory glutamatergic synaptic inputs.r Group II metabotropic glutamate receptors (mGluR) decrease synaptic transmission to pancreas-projecting DMV neurones and modulate PES.r In this study, we show that acute pancreatitis induces a long-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Specifically, we demonstrated that acute pancreatitis decreases the response of glutamatergic synaptic terminals in the DMV to group II mGluR agonist. In contrast, group III mGluRs do not appear to be affected by acute pancreatitis (9). These findings suggest that acute pancreatitis selectively affects DMV neurons involved in the regulation of pancreatic exocrine secretion and further supports the notion that exocrine and endocrine pancreatic secretions are regulated by separate neuronal populations.…”
Section: Evidence For Distinct Regulation Of Endocrine and Exocrine Psupporting
confidence: 74%
See 2 more Smart Citations
“…Specifically, we demonstrated that acute pancreatitis decreases the response of glutamatergic synaptic terminals in the DMV to group II mGluR agonist. In contrast, group III mGluRs do not appear to be affected by acute pancreatitis (9). These findings suggest that acute pancreatitis selectively affects DMV neurons involved in the regulation of pancreatic exocrine secretion and further supports the notion that exocrine and endocrine pancreatic secretions are regulated by separate neuronal populations.…”
Section: Evidence For Distinct Regulation Of Endocrine and Exocrine Psupporting
confidence: 74%
“…Although glutamate is one of the principal neurotransmitters in synapses impinging onto pancreas-projecting DMV neurons, it does not appear to exert a major role on pancreatic functions under control conditions. In fact, microinjections of ionotropic glutamate receptor antagonist kynurenic acid into the DMV do not affect pancreatic exocrine secretion in control rats (9). However, glutamatergic synapses impinging on pancreas-projecting DMV neurons are subject to modulation by various neurotransmitters and hormones (10).…”
Section: Gaba and Glutamatementioning
confidence: 97%
See 1 more Smart Citation
“…Thus, drug effects on mIPSC frequency, especially in the absence of effects on amplitude, were interpreted to be due to actions at receptors located on or near synaptic terminals. Presynaptic modulation of GABA or glutamate release mediated by mGluRs in the DMV and NTS have been described (Jin et al, 2004, Browning and Travagli, 2007, Babic et al, 2012, Babic and Travagli, 2014), but functional iGluR activity at synaptic terminals contacting DMV neurons has been suggested only indirectly. A previous report suggested the presence of iGluRs on GABA terminals in the DMV, but did not identify which receptor types were involved in the response (Derbenev et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, glutamate binds metabotropic glutamate receptors (mGluR) in the DMV to modulate responsiveness of GABAergic presynaptic terminals (Browning et al, 2006, Browning and Travagli, 2007, Babic et al, 2012, Babic and Travagli, 2014). In several brain regions, iGluRs on synaptic terminals (i.e., presynaptic receptors) have been identified functionally as autoreceptors to modulate glutamate release or heteroreceptors to alter GABA release (Berretta and Jones, 1996, Liu et al, 1999, Duguid and Smart, 2004).…”
Section: Introductionmentioning
confidence: 99%